"Paradoxical" EEG response to propofol may differentiate post‐cardiac arrest non‐convulsive status epilepticus from diffuse irreversible cerebral anoxia. Issue 4 (December 2014) - Koutroumanidis, Michalis; Sakellariou, Dimitris; Tsirka, Vasiliki
<x xml:space="preserve">Abstract</x> Current EEG criteria for the diagnosis of non‐convulsive status epilepticus in critically ill patients with repetitive generalised or focal epileptiform discharges primarily rely on a widely accepted low cut‐off frequency limit of 2.5–3 Hz for non‐evolving patterns, or on discharge evolution of frequency, location or mophology. The secondary criterion is a significant clinical or EEG improvement following acute administration of a rapidly acting antiepileptic drug, such as lorazepam. We describe a comatose patient after out‐of‐hospital cardiac arrest, in whom very slow (1‐Hz), non‐evolving generalised periodic epileptiform discharges against an almost completely depressed background would suggest substantial anoxic damage and poor neurological outcome. Yet, reloading with propofol for diagnostic purposes completely dispersed generalised periodic epileptiform discharges and revealed previously absent biological activity, raising the possibility of non‐convulsive status epilepticus that was subsequently confirmed. Brain MRI showed no significant anoxic brain damage and EEG improved, but the patient died from severe cardiopulmonary complications. These observations suggest that in rare cases, slow, non‐evolving generalised periodic epileptiform discharges may reflect non‐convulsive status epilepticus rather than diffuse irreversible cerebral anoxia, while reloading with propofol can be used as an additional secondary diagnostic criterion.